Increase in the range between wet and dry season precipitation - Chou, Chia; Chiang, John C. H.; Lan, Chia-Wei; Chung, Chia-Hui; Liao, Yi-Chun; Lee, Chia-Jung (Nature geoscience, 2013)
The water vapour content of the atmosphere has increased as a result of global warming, strengthening the hydrological cycle. An analysis of observational data suggests that wet seasons have become wetter, and dry seasons drier, in recent decades. Global temperatures have risen over the past few decades. The water vapour content of the atmosphere has increased as a result, strengthening the global hydrological cycle 1 , 2 , 3 , 4 . This, in turn, has led to wet regions getting wetter, and dry regions drier 1 , 2 , 3 , 4 , 5 , 6 . Climate model simulations suggest that a similar intensification of existing patterns may also apply to the seasonal cycle of rainfall 7 . Here, we analyse regional and global trends in seasonal precipitation extremes over the past three decades, using a number of global and land-alone observational data sets. We show that globally the annual range of precipitation has increased, largely because wet seasons have become wetter. Although the magnitude of the shift is uncertain, largely owing to limitations inherent in the data sets used, the sign of the tendency is robust. On a regional scale, the tendency for wet seasons to get wetter occurs over climatologically rainier regions. Similarly, the tendency for dry season to get drier is seen in drier regions. Even if the total amount of annual rainfall does not change significantly, the enhancement in the seasonal precipitation cycle could have marked consequences for the frequency of droughts and floods.